THE WAY FORWARD: SMALLHOLDER FARMERS’ PERSPECTIVE ON MANAGEMENT OF FALL ARMYWORM IN KENYA - Z. Nyakwara; W. Moturi; M. Esilaba (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
Fall Armyworm (FAW) (Spodoptera frugiperda) is a disastrous pest on food crops mainly maize which is the most staple food crops in Africa including Kenya. Since its first arrival in the country by 2016, a lot of crop yield losses had been experienced by smallholder farmers who rely on maize as their main nutritional supplement. To understand smallholder farmers’ counteraction against FAW, a baseline survey was done in eight maize growing counties (Bomet, Busia, Kirinyaga, Makueni, Nakuru, Narok, Taita Taveta and Trans Nzoia) in Kenya. A total of 51 Self Help Groups (SHG) of smallholder farmers were sampled from different agro-ecological zones in order to understand their perspective on management. A structured questionnaire was used to envisage initial responses towards FAW on management. This study showed an ad hoc reaction by smallholder farmers’ on FAW management pathways where a faster means of ridding off any new invasive pest was used. Results indicated a statistical significant association on FAW information and awareness (c2(1) =.392, p<.001) while pesticide usage was significant (c2=14.479(1), p<.05) and effectiveness. Alternative management options were not significant (N=51, p< 0.05). The perspective pathways were impulsive where aftermath impacts were not a factor as long as the problem at hand was managed. FAW is here to stay, and the way forward needs a more sustainable management options which is environmental and human friendly.